Crystal structure, magnetic and dielectric behavior of h-LuMnxO3 +/-delta ceramics (0.95 <= x <= 1.04) - Baghizadeh, A.
Lattice constants, magnetic properties and dielectric behavior of h-LuMnxO3 +/-delta solid solution (0.95 <= x <= 1.04) of bulk ceramic samples prepared by the solid state reaction method were studied to determine the role of stoichiometry changes on the crystalline structure and magneto-electric coupling. It is found that increasing of Mn content results in reduction of cell volume of h-LuMnxO3 +/-delta ceramics mostly due to shrinkage of a-axis length. The antiferromagnetic interactions of Mn3+ ions weaken with cell volume contraction. A weak ferromagnetic contribution appeared in all samples and extends up to the Neel temperature, T-N. Irreversibility in temperature dependent magnetic measurements already reported for stoichiometric compositions of hexagonal RMnO3 oxides appears for all h-LuMnxO3 +/-delta samples right below Neel ordering transition. An increase of magnetic coercive field and magnetization on cooling below T-N in samples is observed in field dependent magnetization and rises as x increases. In addition to the antiferromagnetic ordering transition at T-N, two anomalies of the temperature dependent magnetic susceptibility and dielectric constant are identified below T-N, centered at 69 K and 31 K respectively, being probably due to inhomogeneity of the crystalline structure inside ceramic grains. Changes of the dielectric constant at T-N can be attributed to magneto-electric coupling in the off-stoichiometric hexagonal LuMnxO3+delta lattice. The behavior of the dielectric relaxation follows a thermally activated mechanism with activation energy values characteristic of polaron hoping. (C) 2015 Elsevier B.V. All rights reserved